Impact of the inflation pressure of the tires on lead of front drive wheels and movement resistance force of tractors - Janulevičius, Algirdas; Gurevičius, Povilas (Transport, 2019)
The transmission of mechanical front-wheel drive tractors normally has a front axle lead ratio, which is equal to 1.5…2.5%. Naturally, when ballast masses are added to the tractor or when inflation pressure in the tires is reduced, distortion of the tires is inevitable, which changes the lead of the front wheels. In this paper, we present the impact of tire inflation pressures on the lead front drive wheels and movement resistance force when the tractor travelled with a front drive axle enabled and was engine braking with the fuel supply off. It was found that the variation in front and rear tires inflation pressure combination can significantly change the lead of the front drive wheels. For the tested tractor up to 6.9%. The result is that when the tractor travelled with the front axle enabled and was engine braking, the engine-braking efficiency decreases with increasing lead of the front wheels. Front (slipping) wheels create the opposite-direction torque, which is transferred to the rear wheels through the tractor’s front-rear axle drive system. Additional losses of the engine braking occur in transmission due to power circulation, and the result is that the tractor wheels receive less braking torque from the engine. First published online 8 October 2019